Student Team-Taught Surface Anatomy - Kanani Titchen; Julie Shaner; Karolina Paziana; Duc Vu; Joshua Donohue; Amanda Deming; Vincent Armenti (Association of American Medical Colleges, 2011)
Abstract This resource is a student team-taught surface anatomy program designed to provide a private and professional setting for first-year medical students to learn surface anatomy in small groups, where more time can be committed to answering student questions and concerns. Instructors were second-year medical students who systematically reviewed the relevant anatomy and who were trained in teaching techniques in sessions before the workshops began. This program served several functions. Through it, first-year students were provided a safe and professional setting with adequate time to ask questions about surface anatomy and its applications. They were divided according to gender to allow for more thorough exploration of the anatomy. They were also provided with surgical, clinical, and emergent care contexts for understanding the relevance of surface anatomical landmarks. In addition, the second-year student instructors were required to review the anatomy in preparation for team teaching. In an effort to maximize student participation, both thorax and abdomen workshops were offered on each of 2 nights after regularly scheduled classes had finished. Participation was voluntary. One to two second-year teaching assistants worked with each group of four to five first-year students. Each workshop was 45 minutes in length. At the end of each workshop, first-year student learners filled out anonymous evaluations consisting of Likert-scale items and open-ended questions. According to the evaluations, nearly all of the participants reported that the workshops "enhanced their understanding of the [surface anatomy] material." Likewise, almost all of the students indicated that they would have attended additional workshops had these been offered. Participants consistently reported appreciation for the private, single-gender environment and the focused time spent in learning the surface anatomy.